Rice Crop Manager (RCM) Evaluation Trials in Vietnam - Rakotoson, Tovohery; Nhung, Tran Thi Cam; The, Ngo Duc; Castillo, Rowena; Saito, Kazuki; Hung, Nguyen Van (International Rice Research Institute, 2025)
This report outlines the evaluation of the RCM in Vietnam, focusing on field trials in the MRD. The trials aim to assess the agronomic and economic performance of RCM fertilizer recommendations compared to farmers' practices (FP) and quantify indigenous nitrogen supply and yield response to nitrogen application.